Ensuring the Safety of Objects of National Interests of The Republic of Uzbekistan In the Information Sphere - URAKOVICH, MUKHAMMADIEV JABBOR; MAKHMUT, MAMATOV; GADAYEVICH, GANIYEV ABDUQAHHOR; URAKOVNA, NAMAZOVA MANZURA; SIROJIDDINOVNA, DJALILOVA DILOROM (The journal of contemporary issues in business and government, 2021)
Becoming the object of obligations, information can be included in civil circulation. But relations with respect to information in the public law sphere are no less significant. At any stage in the development of society, information was present as a necessary element in the decision-making process, in the organization of managing individual objects, structures, and the state. However, until recently, the information function has not stood out as an independent function. In the conditions of the formation of the information society, when the role of information is growing immeasurably, when it becomes the main value, the information function is no longer considered only as a real one, but as the main function of the state. Moreover, the state’s information function is aimed at providing information not only to state bodies, but also to citizens, legal entities, and various structures of civil society. It was then that when the orientation of the information function ceased to be limited only by state authorities, it acquired new content, directly affecting the rights and freedoms of the individual, and became fundamental to the state. The constitutional rights and freedoms of man and citizen in the information sphere, their provision are one of the components of the national interests of the Republic of Uzbekistan in accordance with the Law of the Republic of Uzbekistan “On the Concept of National Security of the Republic of Uzbekistan”, approved by the President of the Republic of Uzbekistan on August 29, 1997. According to the law, it is precisely in the realization of the constitutional rights of a person and a citizen to access information, to use information in the interests of carrying out activities not prohibited by law that comprise the interests of the individual in the information sphere. With such an active inclusion of information in social relations, their legal regulation is clearly lagging behind, is characterized by unsystematicity and inconsistency.